The regulation of Islamic banking in Mauritius - Varsha Mooneeram-Chadee (ISRA International Journal of Islamic Finance, 2020)
Purpose: The purpose of this paper is to analyse the main components of the regulatory framework for Islamic banking in Mauritius. This small island state of the Indian Ocean aspires to host Islamic banking products while diversifying the range of financial services offered within its hybrid jurisdiction despite having a minority Muslim population. The study also aims at drawing some comparisons with the well-established regulatory framework that applies to conventional banking. Design/methodology/approach In this qualitative analysis of the regulatory framework of Islamic banking in Mauritius, the doctrinal approach is adopted. This method relies principally on a scrutiny of the provisions of the law and delves into the primary and secondary sources of law guiding Islamic banking practices in the Mauritian jurisdiction. Findings The research study concludes that, with the view of encouraging investors into Islamic banking, policymakers took some regulatory initiatives but these remained timid. These initiatives relied too often on borrowing from the regulatory framework in place for conventional banking practices instead of regulating the area within its own precepts. Prospects for expanding Islamic banking exist but will require more audacious regulatory steps so as to secure the environment within which Islamic banking is to flourish. In the meantime, the industry is in a status quo position with no further legal action currently being envisaged to re-launch this area. Originality/value This research study is among the first generated specifically on the regulatory framework of Islamic banking in a small financial centre that operates mostly offshore financial activities. Previous research work either focused on the empirical analysis or on reviewing the challenges and the prospects but no study has provided an in-depth analysis of the regulatory provisions circumscribing Islamic banking. This lacuna is being filled up by this research paper which highlights the regulatory needs of Islamic banking and comments on the inclusion of and the need for specific rules related to Islamic finance instead of relying on the overlap with conventional banking laws.
Keywords: 330; Banking regulations; Compliance and standards; Corporate governance; Islamic banking; Islamic finance; Mauritian offshore financial centre; Regulatory framework; Transparency